Randomised controlled trial of physiotherapy compared with advice for low back pain. - Frost, H; Lamb, S; Doll, H; Carver, P; Stewart-Brown, S (2004)
OBJECTIVE: To measure the effectiveness of routine physiotherapy compared with an assessment session and advice from a physiotherapist for patients with low back pain. DESIGN: Pragmatic, multicentre, randomised controlled trial. SETTING: Seven British NHS physiotherapy departments. PARTICIPANTS: 286 patients with low back pain of more than six weeks' duration. INTERVENTION: Routine physiotherapy or advice on remaining active from a physiotherapist. Both groups received an advice book. MAIN OUTCOME MEASURES: Primary outcome was scores on the Oswestry disability index at 12 months. Secondary outcomes were scores on the Oswestry disability index (two and six months), scores on the Roland and Morris disability questionnaire and SF-36 (2, 6 and 12 months), and patient perceived benefit from treatment (2, 6, and 12 months). RESULTS: 200 of 286 patients (70%) provided follow up information at 12 months. Patients in the therapy group reported enhanced perceptions of benefit, but there was no evidence of a long term effect of physiotherapy in either disease specific or generic outcome measures (mean difference in change in Oswestry disability index scores at 12 months -1.0%, 95% confidence interval -3.7% to 1.6%). The most common treatments were low velocity spinal joint mobilisation techniques (72%, 104 of 144 patients) and lumbar spine mobility and abdominal strengthening exercises (94%, 136 patients). CONCLUSIONS: Routine physiotherapy seemed to be no more effective than one session of assessment and advice from a physiotherapist.